Inverse‐Tunable Red Luminescence and Electronic Properties of Nitridoberylloaluminates Sr2−xBax[BeAl3N5]:Eu2+ (x=0–2). Issue 12 (2nd February 2022) - Elzer, Eugenia; Strobel, Philipp; Weiler, Volker; Amin, Muhammad R.; Schmidt, Peter J.; Moewes, Alexander; Schnick, Wolfgang
Abstract: The nitridoberylloaluminate Ba2 [BeAl3 N5 ]:Eu 2+ and solid solutions Sr2− x Ba x [BeAl3 N5 ]:Eu 2+ ( x =0.5, 1.0, 1.5) were synthesized in a hot isostatic press (HIP) under 50 MPa N2 atmosphere at 1200 °C. Ba2 [BeAl3 N5 ]:Eu 2+ crystallizes in triclinic space group P 1 ‾ (no. 2) ( Z =2, a =6.1869(10), b =7.1736(13), c =8.0391(14) Å, α =102.754(8), β =112.032(6), γ =104.765(7)°), which was determined from single‐crystal X‐ray diffraction data. The lattice parameters of the solid solution series have been obtained from Rietveld refinements and show a nearly linear dependence on the atomic ratio Sr : Ba. The electronic properties and the band gaps of M 2 [BeAl3 N5 ] ( M =Sr, Ba) have been investigated by a combination of soft X‐ray spectroscopy and density functional theory (DFT) calculations. Upon irradiation with blue light (440–450 nm), the nitridoberylloaluminates exhibit intense orange to red luminescence, which can be tuned between 610 and 656 nm (fwhm=1922–2025 cm −1 (72–87 nm)). In contrast to the usual trend, the substitution of the smaller Sr 2+ by larger Ba 2+ leads to an inverse‐tunable luminescence to higher wavelengths. Low‐temperature luminescence measurements have been performed to exclude anomalous emission. Abstract : The nitridoberylloaluminate Sr2− x Ba x [BeAl3 N5 ]:Eu 2+ ( x =0–2) were synthesized in a HIP under 50 MPa N2 atmosphere at 1200–1400 °C. In contrast to the usual trend, the emission maximum in the prepared samples is inversely shifted to higher wavelengths by the incorporation of the larger cation Ba 2+ .